EVALUASI KINERJA KARYAWAN PADA SUBBAG KEPAGAWAIAN DAN TATA USAHA BALAI BESAR VETERINER WATES - Suci Utami Wikaningtyas; Ika Wahyu Setyawati; Rufaida Setyawati (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
Human resources in this digitalization era have entered into a strategic function not only as a personnel management but also a an asset. The potential of human resources must be utilized as well as possible, so as to be able to provide optimal output for the organization. The objectives of this study are (1) to understand the causes of the level of employee performance in the Employment and Administration Sub-Division of Wates Veterinary Center, and (2) to formulate efforts to improve employee performance in the Employment and Administration Sub-Division of Wates Veterinary Center. This research was conducted using qualitative descriptive methods. Data gathering was done by observation, interview and documentation. The informants of this study were 6 people, representatives from the Financial Sub-Division, Household Sub-Parts and Supplies, Sub-Division of Personnel and Administration. The data gathered was carried out a credibility test using data triangulation methods and technical analysis steps through several stages, namely data reduction, data display and making conclusions. The results of the analysis show the causes of employee in the Sub-Division of Personnel and Administration of the Wates Veterinary Center not optimal, including many tasks outside their main tasks, lack of communication, lack of understanding of the details of their duties, lack of employee motivation from the leader. Whereas the efforts to improve employee performance in the Employment and Administration Sub-Division of the Wates Veterinary Center are paying attention to quality of employee (training or education, coaching and work motivation), other supporting facilities for giving awards and spiritual guidance.